Performance of porous asphalt mixture containing seashell as aggregate replacement - Putra Jaya, Ramadhansyah; Liew, N.; K. A., Masri (Penerbit UMP, 2021)
Porous asphalt pavement is mainly used for parking lots which able to let water to drain through the pavement surface into a stone recharge bed and infiltrate into soils under the pavement. This study is to investigate the performance of seashell in porous asphalt and determine the image analysis. The seashell used in this study is cockle shell. The strength of seashell was determined through the Aggregate Impact Value Test (AIV) and Aggregate Crushing Value Test (ACV). The grade of bitumen used was grade 60/70. The porous asphalt volumetric properties was determined through Marshall Stablity Test. The permeability coefficient of sample that contain seashell as aggregate replacement was determined through Permeability Test. Generally, the results shows that the seashell’s percentage loss (AIV and ACV) is suitable use for porous asphalt mixture, where the percentage of loss for AIV and ACV was 27.84% and 7.65% respectively. Based on the Marshall Test, porous asphalt that containing seashell as aggregate replacement shows a different result, where it had lower stability value and it can increase the bulk density of porous asphalt mixture. Furthermore, the permeability coefficient also increase. The surface of seashell able to bond with bitumen. Lastly, the trend of VFA and VTM value is effected by the surface and position of seashell in the porous asphalt sample.